Damp beech forests on calcareous tufas in the Parsęta River basin (Western Pomerania) - Osadowski, Zbigniew (Biodiversity: Research and Conservation, 2011)
Damp beech forests in the Parsęta River basin (Western Pomerania) constitute a rare and unique type of beechwood community in post-glacial landscape of the Pomerania region. They grow on calcareous soil of pararendzina type formed from calcareous tufas and are characterized by the presence of two orchids Cephalanthera rubra and Neottia nidus-avis accompanied by many rare and endangered plant species occurring in habitats rich in calcium.